When rarity meets complexity - Schimke immuno-osseous dysplasia with nephrotic syndrome: a 15-year longitudinal case report - Sobieszek, Kamil; Zachwieja, Katarzyna (Pediatria Polska - Polish Journal of Paediatrics, 2026)
Schimke immuno-osseous dysplasia (SIOD) is an exceptionally rare autosomal recessive disorder caused by pathogenic variants in the SMARCAL1 gene and characterised by spondyloepiphyseal dysplasia, immuno- deficiency, and progressive renal disease, often presenting as steroid-resistant nephrotic syndrome. Fewer than 100 cases have been reported worldwide. This manuscript describes a male patient with genetically confirmed SIOD, monitored age 4.5–19 years. Early features included growth failure, hyperpigmentation, skeletal abnormalities, moderate T-cell lymphopaenia, and biopsy-proven focal segmental glomerulosclerosis. In adolescence, the disease transitioned to a severe phenotype with end-stage renal disease, recurrent infections, bone marrow failure, and Evans syndrome, reflecting profound immune dysregulation. Despite multidisciplinary management, including renal-replacement therapy and individualised immunological care, the patient’s condition progressively deteriorated and he ultimately died from multi-organ failure. This long-term observation illustrates the evolving natural history of SIOD and the shift from renal disease in childhood to combined immunodeficiency and haematological complications in adolescence.